Treacherous is the night - Huber, Anna Lee (Huber, Anna Lee. Verity Kent mystery., 2018)
"It's not that Verity Kent doesn't sympathize with those eager to make contact with lost loved ones. After all, she once believed herself a war widow. But now that she's discovered Sidney is very much alive, Verity is having enough trouble connecting with her estranged husband, never mind the dead. Still, at a friend's behest, Verity attends a séance, where she encounters the man who still looms between her and Sidney--and a medium who channels a woman Verity once worked with in the Secret Service. Refusing to believe her former fellow spy is dead, Verity is determined to uncover the source of the spiritualist's top secret revelation. Then the medium is murdered--and Verity's investigation is suddenly thwarted. Even Secret Service agents she once trusted turn their backs on her. Undaunted, Verity heads to war-torn Belgium, with Sidney by her side. But as they draw ever closer to the danger, Verity wonders if she's about to learn the true meaning of till death do us part"--